2017
DOI: 10.18632/oncotarget.22801
|View full text |Cite
|
Sign up to set email alerts
|

XPO1 target occupancy measurements confirm the selinexor recommended phase 2 dose

Abstract: XPO1 (exportin 1) is the main nuclear export protein with over 200 different protein cargos. XPO1 is overexpressed in tumor cells and high levels are correlated with poor prognosis. Selective Inhibitor of Nuclear Export (SINE) compounds block nuclear export by inhibiting XPO1. The first SINE compound, selinexor, shows promising anti-cancer activity across hematological and solid tumors in Phase 2 and 3 clinical trials. The 2nd generation SINE compound KPT-8602 is being evaluated as an anti-cancer agent in a Ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 29 publications
(49 reference statements)
0
4
0
Order By: Relevance
“…The data clearly indicate that 20mg/kg are necessary to obtain 50% TO after 48h. These data indicate the importance of the approach to find an optimal regimen for drug testing [12]. Patient samples drawn from a single person treated were analyzed for TO over a time course of 15 days as shown in figure 4C.…”
Section: Target Occupancy (To) In Preclinical and Clinical Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…The data clearly indicate that 20mg/kg are necessary to obtain 50% TO after 48h. These data indicate the importance of the approach to find an optimal regimen for drug testing [12]. Patient samples drawn from a single person treated were analyzed for TO over a time course of 15 days as shown in figure 4C.…”
Section: Target Occupancy (To) In Preclinical and Clinical Researchmentioning
confidence: 99%
“…Lysates comprising respective proteins were incubated with increasing concentrations of fluorescently labeled NT(8-13) and analyzed by FCCS. Fig 2A: Dose dependent increase in complex formation of GFP fusions of NTR1 and its derivatives to Dy647-NT(8)(9)(10)(11)(12)(13). The stabilizing triple mutant TTM shows the highest affinity, followed by single mutant A85L.…”
mentioning
confidence: 99%
“…In addition, XPO1 is responsible for selectively transporting certain subsets of mRNAs, miRNA, and snRNA through exporting several RNA-binding proteins and adaptor proteins [ 119 , 120 ]. For example, XPO1: (1) selectively mediates the alternative export of both m 7 G-capped mRNAs and snRNA by binding to CBC20/80 [ 121 ]; (2) preferentially exports a subset of mRNAs encoding oncoproteins, such as Myc, CDC25A, BRD4, Bcl-2, Bcl-6, Mcl-1, Bcl-xL, cyclins, androgen receptor, and Pim1 by exporting several RNA-binding proteins, including LRPPRC, eIF4E, NXF3, and HuR; XPO1 thereby regulates the translation of these oncoproteins [ [121] , [122] , [123] , [124] , [125] , [126] , [127] , [128] , [129] ]; (3) exports U-snRNAs into the cytoplasm for modification and assembly, thus playing a critical role in the regulation of mRNA splicing through binding the adaptor protein PHAX; and (4) mediates the alternative export of both microRNAs and tRNAs.…”
Section: Targeting Xpo1 For Rr-mm Treatmentmentioning
confidence: 99%
“…One can argue that the pancreatic tumor-associated stroma may hinder appropriate delivery of selinexor to the tumor site. In this direction, using in vivo mouse studies, XPO1 occupancy could be measured in tumors (non-pancreatic model) and was found to be dose-dependent, with >90% target saturation at 10 mg/kg (which is equivalent to ~50 mg flat dose in humans) [ 91 ]. Drug-target occupancy was measured in a dose-response time course and full occupancy occurred by 6 h at all doses.…”
Section: Activity Of Sine In Pancreatic Cancermentioning
confidence: 99%